Análise exergética e termoeconomia: sistematização crítica da produção científica - Tuna, Celso Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This text describes the lines of research in which the author acted after his doctorate related to the energy area covering the following topics: exergetic analysis and exergoeconomic analysis. The scientific productions described herein were results obtained from the author's research and guidance from graduate students, besides the results of collaborations with other researchers from the research group that participates. Among the main contributions of the articles published, are the development and application of exergoeconomic analysis for various configurations of thermal and electrical generation systems, and also the participation in the construction of a biogas steam reformer prototype and a fluidized bed gasifier in the Energy Systems Optimization Laboratory of UNESP, Guaratinguetá campus. The author is classified in the Scopus base with an h index of 9, and in Google scholar with an h index equal to 11, demonstrating the relevance of its 19 publications in indexed journals with high impact factor

Este texto descreve as linhas de pesquisa em que o autor atuou após o seu doutorado relacionadas a área de energia, abrangendo os seguintes tópicos: análise exergética e análise exergoeconômica. As produções científicas aqui descritas foram resultados obtidos a partir das pesquisas do autor e de orientações de alunos de pós-graduação, além de resultados de colaborações com outros pesquisadores do grupo de pesquisa que participa. Dentre as principais contribuições dos artigos publicados, estão o desenvolvimento e aplicação de metodologia de análise exergoeconômica para diversas configurações de sistemas de geração de energia térmica e elétrica, e também a participação na construção de um protótipo reformador a vapor de biogás e de um gaseificador de leito fluidizado no Laboratório de Otimização de Sistemas Energéticos da UNESP, campus de Guaratinguetá. O autor está classificado na base Scopus com um índice h igual a 9, e no Google Acadêmico com um índice h igual a 11, demonstrando a relevância de suas 19 publicações em revistas indexadas de elevado fator de impacto
Exergetic analysis and thereconomics: critical systematization of scientific production
Keywords: Exergy; Exergetic analysis; Thermoeconomics; Exergoeconomics; Energia eletrica e calor - Cogeração; Análise energética; Analise termica; Calor - Armazenamento; Heat storage